2019
DOI: 10.1186/s12906-019-2703-5
|View full text |Cite
|
Sign up to set email alerts
|

Qingkailing injection ameliorates cerebral ischemia-reperfusion injury and modulates the AMPK/NLRP3 Inflammasome Signalling pathway

Abstract: BackgroundCerebral ischemia is the second-leading cause of death and the main cause of permanent adult disabilities worldwide. Qingkailing (QKL) injection, a patented Chinese medicine approved by the China Food and Drug Administration, has been widely used in clinical practice to treat cerebral ischemia in China. The NOD-like receptor pyrin 3 (NLRP3) inflammasome is activated in cerebral ischemia and thus, is an effective therapeutic target. AMP-activated protein kinase (AMPK) is an important regulator inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 45 publications
2
34
0
Order By: Relevance
“…Ischemia/reperfusion injury is considered as a brain and blood vessel complication trigged by the thrombolysis treatment to ischemic stroke, which has given a severe threat to human health and happiness. Recent research studies have shown that several traditional Chinese medicines and edible plants, such as Qingkailing injection [ 16 ], Yiqi Tongluo granule [ 17 ], and Crepidiastrum denticulatum extract [ 18 ], could relieve ischemia/reperfusion injury. Punica granatum L. is an edible fruit with plenty of bioactivities for hundreds of years.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia/reperfusion injury is considered as a brain and blood vessel complication trigged by the thrombolysis treatment to ischemic stroke, which has given a severe threat to human health and happiness. Recent research studies have shown that several traditional Chinese medicines and edible plants, such as Qingkailing injection [ 16 ], Yiqi Tongluo granule [ 17 ], and Crepidiastrum denticulatum extract [ 18 ], could relieve ischemia/reperfusion injury. Punica granatum L. is an edible fruit with plenty of bioactivities for hundreds of years.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK is mainly responsible for peripheral energy balance, fat metabolism and ATP conservation and synthesis. 35 AMPK has frequently been referred to as the "metabolic master switch", and it has the ability to be rapidly activated by anti-inflammatory stimuli. 13 When the cell energy supply is reduced, AMPK can be activated to enhance energy production 14 and represents a potential protective mechanism in the early stages of cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, CIRI could stimulate dangerous molecular signals in the body, stimulate extracellular and intracellular pattern recognition receptor signals, thus inducing excessive release of inflammatory mediators, leading to neuronal apoptosis. 31 TNF-α and IL-6 are typical representatives of proinflammatory factors, which will aggravate the inflammatory injury of CIRI. IL-10 is an anti-inflammatory medium that helps prevent inflammation.…”
Section: Discussionmentioning
confidence: 99%